Nursing of a patient with large hematoma after prcutaneous coronary intervention for acute myocardial infarction (1例急性心肌梗死患者PCI术后并发大面积血肿的护理) - LU Xinyue (陆馨悦) (中西医结合护理)
This paper summarized the experience of nursing of a patient with large hematoma after prcutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). Key issues of nursing included monitoring and nursing of hematoma, prevention of hemorrhagic shock included by arterial hemorrhage, early diagnosis and warning of blood vessel vasovagal reflex, pharmaceutical administration and exercise guidance. (本文总结1例急性心肌梗死患者PCI术后并发大面积血肿的护理体会, 包括血肿的观察及护理, 预防动脉出血和失血性休克, 迷走神经反射早期识别及预警, 药物管理, 运动指导等。)